PENAKSIR PRODUK YANG EFISIEN UNTUK RATA-RATA POPULASI PADA SAMPLING ACAK SEDERHANA MENGGUNAKAN KOEFISIEN VARIASI DAN KOEFISIEN KURTOSIS - Isnaini '; Arisman Adnan; Rustam Efendi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article reviews  three product estimators  for the population mean in  simple random sampling.  They  use the  coefficient of variation and  coefficient of kurtosis  of auxiliary variables. This article  is the reviewof  Singh’s article [Jour. Ind. Soc.  Ag. Statistics 56(3): 267-275]. Those three estimators are biased. Then their Mean Square Error(MSE) are determined. Furthermore,  MSE  of each estimator is compared to obtain the most efficient estimator.  This  study  shows  that the  modification of  the product  estimator  is the most efficient estimator if the conditions are met.